Sequence and Nuclease Requirements for Breakage and Healing of a Structure-Forming (AT)n Sequence within Fragile Site FRA16D - Kaushal, Simran (Cell Rep, 2019)
Common fragile sites (CFSs) are genomic regions that display gaps and breaks in human metaphase chromosomes under replication stress and are often deleted in cancer cells. We studied an ~300-bp subregion (Flex1) of human CFS FRA16D in yeast and found that it recapitulates characteristics of CFS fragility in human cells. Flex1 fragility is dependent on the ability of a variable-length AT repeat to form a cruciform structure that stalls replication. Fragility at Flex1 is initiated by structure-specific endonuclease Mus81-Mms4 acting together with the Slx1–4/Rad1–10 complex, whereas Yen1 protects Flex1 against breakage. Sae2 is required for healing of Flex1 after breakage. Our study shows that breakage within a CFS can be initiated by nuclease cleavage at forks stalled at DNA structures. Furthermore, our results suggest that CFSs are not just prone to breakage but also are impaired in their ability to heal, and this deleterious combination accounts for their fragility.